Animal modes of cognitive impairment (CRC/Taylor & Francis, 2006)
The costs associated with a drug’s clinical trials are so significant that it has become necessary to validate both its safety and efficacy in animal models prior to the continued study of the drug in humans. Featuring contributions from distinguished researchers in the field of cognitive therapy research, Animal Models of Cognitive Impairment examines some of the most popular and successful animal archetypes used in the context of drug discovery. It provides integrated coverage of the latest research concerning neuronal systems relevant to cognitive function and dysfunction, assimilating reviews of this research within the context of each chapter. This approach is unique in that it brings together molecular and neurochemical methodologies, behavioral applications in translational models, and clinical applications. The book comprehensively discusses a wide variety of animal models of cognitive impairment, including genetic, lesion, pharmacological, and aging related impairments. Italso explores the significance of this research in regards to the treatment of various addictions and disorders such as stroke, autism, Alzheimer’s, schizophrenia, and ADHD.